Black males in secondary and postsecondary education teaching, mentoring, advising and counseling - Fletcher, Edward C.; Hines, Erik M.; Lewis, Chance W.; Moore, James L. (Emerald Publishing Limited, 2023)
Black males face several active and inactive discriminations across society. In education, they encounter stiffer disciplinary actions such as out of school suspension and expulsion than their White peers, are overrepresented in special education programs as well as over diagnosed; are underrepresented in gifted in talented programs; advanced placement and honors courses; and have the lower college graduation rates compared to other racial groups. Although these issues are barriers to Black male success, we know that for every challenge, there is a solution to improving academic, career, and life outcomes for Black males. Black Males in Secondary and Postsecondary Education contributes to the existing literature on this population with a focus on teaching, mentoring, advising, and counseling Black boys and men, from preschool to graduate/professional school and beyond into their careers. The chapter authors address the gap on research from a strengths-based perspective, around implications of the COVID-19 pandemic on Black male educational attainment, the increased anti-black racism around police racial profiling and disciplinary issues in education, and academic and career outcomes of Black males. More importantly, the chapter authors provide recommendations for policy, practice and research.
Includes index.